Extent to which the content of the Hadith courses for the secondary stage included the values of tolerance in the Kingdom of Saudi Arabia - Alkathiri, Mousa Abdullah; Bani Atta, Suhad Abdullah (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the extent to which the content of the speech course for the secondary stage includes the values of tolerance in the KSA, by revealing the tolerance values that can be used in the speech course of the secondary stage in the fields (religious, moral, social, economic and environmental, scientific, security and legal, intellectual and cultural) and to achieve the objectives of the study, a preliminary list was prepared that included (115) values that must be included in the content The Noble Hadith curriculum, and in light of the opinions of the arbitrators, the researcher came up with a list of tolerance values for content analysis that consisted of (6) areas, the study concluded that the degree of inclusion of phrases related to the values of tolerance in the religious and moral sphere is one of the most common areas of tolerance values included in the hadith course for the secondary stage at a rate of (46.48%) and a moderate degree of inclusion, while the rest of the fields were in a weak degree of inclusion, ranked: the economic and environmental field (13.82%); the social (12.45%); the security and (12.00%); scientific (8.97%) and the intellectual and cultural field (6.28%).